(untitled) (Journal of Contemporary Philology, 2025)
This paper addresses Salman Rushdie’s idea of migrancy as a literary version of Giorgio Agamben’s notion of profanation. Contrary to Agamben, who refers to profanation based on the sacred man (homo sacer), Rushdie’s work shows that profanation or impurity is at hand through migrancy. It displays, surveys, and discusses migrancy as an ambivalent reality which does not only embody the potential of uplifting human condition, but also reinforces and nourishes ostracisms. This paper argues for continuous cultural negotiation and renewal required by migratory rationality to uplift life quality in human condition. Theoretically, an intersectional approach that looks at “relationships among seemingly different phenomena” is convoked to examine the intellectual affiliations between Rushdie and Agamben. Rushdie being a writer and Agamben a philosopher, the paper implicitly pleas for the necessary reinforcement of connections between all subjects, like literature and philosophy, in the field of humanities in academia. The study itself consists of three sections. The first section deals with the significance of migrancy in Rushdie’s work. The second section deals with Rushdie’s novel The Satanic Verses. It addresses the relationship existing between migrancy and impurity in the novel. It also displays consequences of common perceptions about impurity in today’s cultural or ideological constellations. The last section deals with the scholarly affiliation of Rushdie’s impurity with Agamben’s profanation. It ends with discussion of impurity/profanation’s prospects in the ‘community to come.’